Genetic analysis of male reproductive success in relation to density in the zebrafish, Danio rerio - Spence, Rowena (BioMed Central, 2006)
BACKGROUND: We used behavioural and genetic data to investigate the effects of density on male reproductive success in the zebrafish, Danio rerio. Based on previous measurements of aggression and courtship behaviour by territorial males, we predicted that they would sire more offspring than non-territorial males. RESULTS: Microsatellite analysis of paternity showed that at low densities territorial males had higher reproductive success than non-territorial males. However, at high density territorial males were no more successful than non-territorials and the sex difference in the opportunity for sexual selection, based on the parameter I(mates), was low. CONCLUSION: Male zebrafish exhibit two distinct mating tactics; territoriality and active pursuit of females. Male reproductive success is density dependent and the opportunity for sexual selection appears to be weak in this species.